2005
DOI: 10.1021/bi048838c
|View full text |Cite
|
Sign up to set email alerts
|

Dimeric Transthyretin Variant Assembles into Spherical Neurotoxins

Abstract: Familial amyloidotic polyneuropathy is a hereditary autosomal-dominant disease in which the deposited transthyretin fibrils are derived from amyloidogenic mutation. We investigated structure and stability of a human Ser112Ile transthyretin variant and showed that the Ser112Ile variant exists as a dimer having nonnative tertiary structure at physiological pH. In addition, the dimeric Ser112Ile assembles into a spherical aggregate and exerts cytotoxicity in a human neuroblastoma cell line. Our results suggest th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…2a). The difference in mass between the labeled and unlabeled protein was ϳ3 kDa, enabling us to resolve these species in spectra, with peaks corresponding to the 14ϩ to 16ϩ charge states of 12 C-14 N and 13 C-15 N intact homotetramers. In addition, peaks at high m/z values were assigned to a range of higher oligomers.…”
Section: Mass Spectrometry Of An Isotopically Labeled Transthyretinmentioning
confidence: 99%
See 1 more Smart Citation
“…2a). The difference in mass between the labeled and unlabeled protein was ϳ3 kDa, enabling us to resolve these species in spectra, with peaks corresponding to the 14ϩ to 16ϩ charge states of 12 C-14 N and 13 C-15 N intact homotetramers. In addition, peaks at high m/z values were assigned to a range of higher oligomers.…”
Section: Mass Spectrometry Of An Isotopically Labeled Transthyretinmentioning
confidence: 99%
“…Support for this hypothesis comes from investigations of a dimeric variant that is prone to amyloid formation (11) and another that forms cytotoxic spherical aggregates (12). Spin labeling experiments have demonstrated that many of the interactions found in the native transthyretin dimer are maintained in fibrils (13).…”
mentioning
confidence: 99%
“…Furthermore, to more accurately model the properties of human TTR, it is desirable to remove the polyhistidine tag prior to experimentation since it can alter protein structure and influence aggregation properties, particularly when divalent cations are present. Biophysical studies using 2-mercaptoethanol-bound and polyhistidine-tagged rTTR [11,18,19] may yield results that deviate significantly from identical studies conducted on native sequence rTTR containing a free thiol group. In addition, our results suggest that mass spectrometric analysis of any expression product is essential when using reductants to optimize the yield of recombinant systems.…”
Section: Discussionmentioning
confidence: 82%
“…Tissue-deposited ATTR was extracted as previously described (11 ). Recombinant TTRs were expressed and purified as described previously (12 ). We analyzed samples using 3 different ProteinChip surfaces: a 7 Nonstandard abbreviations: FAP, familial amyloidotic polyneuropathy; ATTR, amyloidogenic transthyretin; TTR, transthyretin; MS, mass spectrometry; WT, wild-type; CSF, cerebrospinal fluid.…”
Section: Resultsmentioning
confidence: 99%